Peningkatan Kualitas dan Daya Tarik Taman Wisata Air Paggora: Redesain melalui Memori Kolektif Masyarakat - Setijanti, Purwanita; Cahyadini, Sarah; Setyawan, Wahyu; Septanti, Dewi; Retno Utami, Adinda Sih Pinasti; Ula, Zuhrotul Mawaddatil; Faizin, Muchammad Indra; Firdaus, Achmad Ichsan; Yaqin, Muhammad Ainul; Sulistiastuti, Mutia (Universitas Syiah Kuala, 2024)
Paggora Water Park, a once-popular tourist destination, has experienced significant degradation in its facilities and infrastructure due to the prolonged COVID-19 lockdown. This paper examines the urgent need for comprehensive renovation and tourism design concepts to restore and enhance the park's appeal based on the opinions of Paggora Water Tourism visitors using quantitative methods, which will be analyzed using multiple linear regression techniques, ultimately providing a design concept that will fit with the service quality and visitor satisfaction. Five independent variables will be tested with the dependent variable (visitor satisfaction): tangible, reliability, responsiveness, assurance, and empathy. The results of the quantitative analysis show that the variables influencing visitor satisfaction are the tangible (positive influence) and the assurance variable (negative influence). The proposed design concept aims to apply the results of survey and quantitative analysisimproving facilities or physical forms to increase visitor satisfactioncreating an engaging and memorable visitor experience. These findings also highlight the renovation process that the team undertook and the potential for Paggora Water Park to serve as a model for similar facilities facing maintenance and resource challenges